Periodontal ligament stem/progenitor cells with protein-releasing scaffolds for cementum formation and integration on dentin surface. (1st November 2016) - Cho, Hankyu; Tarafder, Solaiman; Fogge, Michael; Kao, Kristy; Lee, Chang H.
ABSTRACT: Purpose/Aim : Cementogenesis is a critical step in periodontal tissue regeneration given the essential role of cementum in anchoring teeth to the alveolar bone. This study is designed to achieve integrated cementum formation on the root surfaces of human teeth using growth factor–releasing scaffolds with periodontal ligament stem/progenitor cells (PDLSCs). Materials and methods : Human PDLSCs were sorted by CD146 expression, and characterized using CFU-F assay and induced multi-lineage differentiation. Polycaprolactone scaffolds were fabricated using 3D printing, embedded with poly(lactic-co-glycolic acids) (PLGA) microspheres encapsulating connective tissue growth factor (CTGF), bone morphogenetic protein-2 (BMP-2), or bone morphogenetic protein-7 (BMP-7). After removing cementum on human tooth roots, PDLSC-seeded scaffolds were placed on the exposed dentin surface. After 6-week culture with cementogenic/osteogenic medium, cementum formation and integration were evaluated by histomorphometric analysis, immunofluorescence, and qRT-PCR. Results : Periodontal ligament (PDL) cells sorted by CD146 and single-cell clones show a superior clonogenecity and multipotency as compared with heterogeneous populations. After 6 weeks, all the growth factor–delivered groups showed resurfacing of dentin with a newly formed cementum-like layer as compared with control. BMP-2 and BMP-7 showed de novo formation of tissue layers significantly thicker than all the other groups, whereas CTGF and BMP-7 resulted in significantly improved integration on the dentin surface. The de novo mineralized tissue layer seen in BMP-7-treated samples expressed cementum matrix protein 1 (CEMP1). Consistently, BMP-7 showed a significant increase in CEMP1 mRNA expression. Conclusion : Our findings represent important progress in stem cell–based cementum regeneration as an essential part of periodontium regeneration.